Impact of Employee Engagement on Organizational Commitment and Performance: A Review of Private Companies in Bangladesh - Islam, Muhaiminul; Islam, Saiful (Dhaka University Journal of Business Studies, 2021)
This study explores the relationship between employee engagement and organizational commitment and performance in the context of Bangladeshi private organizations. Data has been collected from a sample of 300 employees who have already completed two years of their tenure in the current organizations using a twostage sampling process where a simple random sampling is used to select food and beverage companies in the first stage, and a judgmental sampling is used to select respondents from those organizations in the second stage. Pearson's correlation matrix and regression analysis are performed to predict and estimate the relationships among employee engagement, organizational commitment, and organizational performance. Besides, employee engagement is measured by considering four critical dimensions: workplace involvement, engagement practice, work-life balance, and employee retention. Findings show that workplace involvement and employee retention are the most significant drivers among these four dimensions. Employee engagement has a significant impact on organizational commitment but a fewer impact on organizational performance. This study significantly contributes to the existing employee management knowledge, both academically and practically. Journal of Business Studies, Vol. XLII, No. 1, April 2021 Page 41-58